ANALISIS PERPINDAHAN PANAS TUNGKU KRUSIBEL PELEBURAN ALUMINIUM PADA LABORATORIUM TEKNIK MESIN UNIDAYAN - La Baride; Muhamad Iqbal Achmad; La Andika; Noor Dhani (POLITALA PRESS, 2022)
Heat transfer plays an important role in the metal smelting process, so it is important for analysis to be carried out. This study aims to analyze heat transfer in a charcoal-fueled crucible furnace equipped with a blower in the mechanical engineering laboratory, Dayanu Ikhsanuddin University. The experimental method in this study was carried out at a furnace crucible burned with mangrove charcoal and equipped with a blower as a channel to circulate air through a 2-inch tube. Based on the results of the study, the heat from mangrove charcoal fuel is 37985.364kJ, the heat of smelting of aluminum is 1635.24kJ, and the heat absorbed by the walls and cover of the furnace is 29152.76kJ. The heat escaping through the cover, chimney, and other losses is 7197.37 kJ. The efficiency of the charcoal-fueled crucible furnace is 81.05%.